Kebijakan Pajak Dan Keuangan Publik Di Negara-Negara Muslim Selama Pandemi Covid-19: Perbandingan Uni Emirat Arab Dan Qatar - Udiyo Basuki; Slamet Haryono (Universitas Sang Bumi Ruwa Jurai, 2023)
The Coronavirus (Covid-19) pandemic, which was caused by the SARS-CoV-2 virus since the beginning of 2020, has spread throughout the world. Due to the spread of this virus, the world is experiencing a health emergency, considering the large number of deaths caused by infected victims. The World Health Organization, WHO declared Covid-19 a pandemic on March 11, 2020. All affected countries immediately adopted policies to contain the spread of the virus, including the United Arab Emirates and Qatar, which are countries with the most open economic policies in the world. Various policies, especially policies in the field of taxation and public finance were taken by the Governments of the United Arab Emirates and Qatar to overcome the impact of the pandemic. The whole world that has a tax regime is engaged in a virus mitigation strategy.The research, which uses a combination of field research and library research, is analytically descriptive in nature, namely describing and analyzing the responses of the governments of the United Arab Emirates and Qatar regarding tax policy and the use of tax proceeds during the Covid-19 pandemic.The results of the research show that to deal with the consequences of the Covid-19 pandemic which has an impact on almost all sectors of life, the governments of the United Arab Emirates and Qatar have both taken strategic steps, including in tax policy. They issue various regulations related to taxation in terms of collecting tax funds and using tax funds through the state budget.